Edge decorative motif (Kok) Kelingkan embroidery of Kelantan - Norhasliyana Hazlin Zainal Amri; Azwady Mustapha; Hanisa Hassan; Hamdzun Haron (AIP Publishing, 2021)
Kelingkan is an art of embroidery using metal ribbon threads coated with gold, silver embroidered on a soft fabric surface. Kelingkan requires high precision and uses the expertise of embroiders. Recall this is the handcraft led by Malay women for a long time in nature, namely Malays in Sarawak, Kelantan and Selangor. Each of these states has a different design motif identity and reflects its own state and identity through the use of flora and fauna motifs. In Kelantan, the art of embroidery is still done on a small scale although it is less well known Sarawak and Selangor but the market demand still continues due to the uniqueness of the edge decoration (kok) different between the states that are active in Kelingkan embroidery. The question is what is the origin of Kelantan embroidery and how is the decorative motif (kok) depicted in Kelantan embroidery? To answer this question, a qualitative study was conducted through field study methods, Such as observation of dry embroidery artifacts and interviews with embroidery markers. The study found that a history of embroidery kelingkan in Malaysia evolved since the existence of the trading system in Malaya. Only three states Sarawak, Selangor and Kelantan still have embroiders that are actively conducing it. The development of kelingkan embroidery in Malaysia started in the palace and developed through hereditary family relationships and incubator program while there are two side decorative motifs (kok) depicted in Kelantan kelingkan embroidery, namely 3 points and 5 points or also known as etok is shell. In conclusion, the results of this study should be seen as a continuing source for the Malay community art treasures to be preserved and maintained at the younger generation so that no time wasted. Through this study, kelingkan embroidery can also explain the variety of kelingkan available in Malaysia, Kelantan, Selangor and Sarawak which are still actively doing this embroidery in textile and clothing.